Corneal sensitivity in healthy bovine calves. (27th March 2014) - Tofflemire, Kyle L.; Whitley, Elizabeth M.; Dewell, Renee D.; Gould, Stacie A.; Allbaugh, Rachel A.; Ben‐Shlomo, Gil; O'Connor, Annette M.; Whitley, Robert D.
<x xml:space="preserve">Abstract</x> Objective To evaluate corneal sensitivity as measured by the corneal touch threshold in healthy bovine calves. Animals Studied Twelve clinically normal male calves with predominantly Holstein genetics and a median age of 76.5 days (range, 67–92 days). Procedures Corneal touch threshold (CTT) of the central cornea was measured in both eyes of each calf using a Cochet‐Bonnet aesthesiometer. Results The mean ± standard deviation corneal touch threshold of all eyes was 1.33 ± 1.1 g/mm2 (range, 0.62–66.15 g/mm2), corresponding to a filament length of 34.56 ± 8.02 mm (range, 14–47.5 mm). There was no significant difference between fellow eyes. Conclusions Cochet‐Bonnet aesthesiometry was well tolerated in all 12 calves using a modified head restraint. Calves in this study may have a relatively sensitive central cornea compared to adult cattle and some other species; however, wide variation among individuals and eyes may be possible. Studies utilizing larger calf populations are necessary to establish reference ranges.